Magnetism and orbitally driven spin-singlet states in Ru oxides: A muon-spin rotation study - Blundell, S; Lancaster, T; Baker, P; Hayes, W; Pratt, F; Atake, T; Rana, D; Malik, S (2008)
We have used zero-field muon-spin rotation to study the local magnetic properties of SrRu O3, Y2 Ru2 O7, and La2 Ru O5. While SrRu O3 and Y2 Ru2 O7 give rise to coherent precession signals, in La2 Ru O5 we find no signature of long range magnetic order below the structural transition, but observe relaxation consistent with that expected due to a dimerization into spin-singlet states. In Y2 Ru2 O7 we observe two precession signals with different temperature dependences, consistent with the nature of the noncollinear ordering being temperature dependent. © 2008 The American Physical Society.